1984
DOI: 10.1007/bf00140047
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Butanediol production from xylose and other hemicellulosic components by Bacillus polymyxa

Abstract: In the xylose fermentation of Bacillus polymyxa strain 9035, best 2,3-butanediol yields were obtained with 1.0% yeast extract, 4-6% xylose, shaking at 125 rpm and incubation at 30°C.Under these conditions, mannose, galactose, L-arabinose, cellobiose, starch and glucose were readily metabolized and yielded significant amounts of diol.Diol production from xylan was also demonstrated. In addition, the screening of a number of B___tpolymyxa strains on xylose revealed that only strains 9031-1 and 9035 used xyiose e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 12 publications
3
12
0
1
Order By: Relevance
“…As shown in Table 2, 2,3-BD was found to increase with increasing initial glucose concentrations, but the specific 2,3-BD productivity decreased at high substrate concentrations, which indicated that at low sugar concentrations the fermentation proceeded rapidly to completion, on the other hand, higher glucose concentrations fermentations were less efficient. Similar results were reported by Laube et al [15] and Fages et al [16] for B. polymyxa fermentation, Alam et al [17] for B. amyloliquefaciens and Perego [18] for E. aerogenes.…”
Section: Effect Of Initial Glucose Concentration On 23-bd Productionsupporting
confidence: 87%
“…As shown in Table 2, 2,3-BD was found to increase with increasing initial glucose concentrations, but the specific 2,3-BD productivity decreased at high substrate concentrations, which indicated that at low sugar concentrations the fermentation proceeded rapidly to completion, on the other hand, higher glucose concentrations fermentations were less efficient. Similar results were reported by Laube et al [15] and Fages et al [16] for B. polymyxa fermentation, Alam et al [17] for B. amyloliquefaciens and Perego [18] for E. aerogenes.…”
Section: Effect Of Initial Glucose Concentration On 23-bd Productionsupporting
confidence: 87%
“…In contrast, there is little room for yield improvement, since as much as 95% of the energy in the substrate can be recovered in products with current technologies. 2,3‐Butanediol is a bulk chemical employed as antifreezing agent, solvent, fuel, fuel additive, as an intermediate for the manufacture of chemicals and as a building block for synthetic polymers and resins. It can be produced from xylose or xylose‐containing hydrolyzates by Klebsiella pneumoniae or Klebsiella oxytoca 27,28 at 90% of the theoretical yield (0.5 g/g), or from mannose with Bacillus polymyxa 29. Product recovery is desirably carried out by extraction instead distillation, owing to its high boiling point. 1,3‐Propanediol, also called β‐propylene glycol, is used as a solvent, in the manufacture of adhesives and polyesters, and as a building block for the production of polymers such as polytrimethylene terephthalate.…”
Section: Lcm Fractionation In Aqueous Mediamentioning
confidence: 99%
“…In the comparison of productivity with different bacteria species and substrates shown in Table 6, it was found that with the optimal medium, BA production and productivity were higher than with other media in batch fermentation (Grover et al, 1990;Cao et al, 1997;Jiang et al, 2013). Compared with the utilization of xylose, BA production in this study was higher than in other studies (Jansen et al, 1984;Laube et al, 1984). In fed-batch fermentation, BA production with xylose solution was lower than with glucose or other pure substrates (Ji et al, 2010;Zhang et al, 2010).…”
Section: Batch and Fed-batch Fermentations (5-l Bioreactor)mentioning
confidence: 55%